2014
DOI: 10.1128/jvi.00929-14
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Activity of Avian Influenza Virus in Human Pancreatic Ductal Adenocarcinoma Cell Lines

Abstract: Pancreatic ductal adenocarcinoma (PDA) is the most lethal form of human cancer, with dismal survival rates due to late-stage diagnoses and a lack of efficacious therapies. Building on the observation that avian influenza A viruses (IAVs) have a tropism for the pancreas in vivo, the present study was aimed at testing the efficacy of IAVs as oncolytic agents for killing human PDA cell lines. Receptor characterization confirmed that human PDA cell lines express the alpha-2,3-and the alpha-2,6-linked glycan recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 82 publications
1
21
1
Order By: Relevance
“…To test the feasibility of this approach, we engineered a new H7N3 NS1-77 virus in which the genes expressing the surface antigens haemagglutinin (HA) and neuraminidase (NA) were replaced with those of the well characterized human strain H1N1 A/ Puerto Rico/8/1934 (PR8). In vitro experiments performed using this 6 : 2 recombinant virus, termed PR8 H1/N1-2962 NS1-77, confirmed that the exchange of surface antigens did not alter the virus' ability to trigger apoptosis in BxPC-3 cells at levels similar to the parental strains and thus, in line with previous data (Kasloff et al, 2014), at higher levels compared to the H1N1 PR8 virus (Fig. 6a).…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecsupporting
confidence: 75%
See 4 more Smart Citations
“…To test the feasibility of this approach, we engineered a new H7N3 NS1-77 virus in which the genes expressing the surface antigens haemagglutinin (HA) and neuraminidase (NA) were replaced with those of the well characterized human strain H1N1 A/ Puerto Rico/8/1934 (PR8). In vitro experiments performed using this 6 : 2 recombinant virus, termed PR8 H1/N1-2962 NS1-77, confirmed that the exchange of surface antigens did not alter the virus' ability to trigger apoptosis in BxPC-3 cells at levels similar to the parental strains and thus, in line with previous data (Kasloff et al, 2014), at higher levels compared to the H1N1 PR8 virus (Fig. 6a).…”
Section: The Immunostimulatory Activity Of H7n3 Ns1-77 Virus In Infecsupporting
confidence: 75%
“…Avian-origin influenza A viruses (IAVs) were previously shown to infect and induce potent apoptosis of various PDA cell lines, including BxPC-3 cells (Kasloff et al, 2014) in which different viruses displayed reduced oncolytic effect compared to other malignant pancreatic cells (Lee et al, 2014;Murphy et al, 2012). These observations suggested that avian influenza isolates might be a useful treatment option for specific subclasses of PDA.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations